Lymphoepithelial carcinoma in the sublingual gland. Issue 7 (July 2022) - Mong, L.-C.; Liu, K.-F.; Lin, Y.-H.; Wu, C.-Y.
Abstract: Lymphoepithelial carcinoma is rare in the salivary glands, with an incidence of 0.4%. The most commonly affected site is the parotid gland, followed by the submandibular gland. Lymphoepithelial carcinoma in the sublingual gland has been reported only four times in the existing English-language literature. Such tumours are characterized by the presence of a poorly differentiated carcinoma that is surrounded and infiltrated by lymphocytes, and they are strongly associated with Epstein–Barr virus infection, patient ethnicity, and prominent radiosensitivity. Wide surgical excision combined with adjuvant therapy has been suggested as the first-choice therapeutic regimen. This report describes the case of a 34-year-old Indonesian woman who was evaluated and treated in Taipei Medical University Hospital. She had a tumour that presented as a painless swelling on the floor of the mouth. The diagnosis was confirmed by conducting an incisional biopsy, and a wide surgical excision with bilateral supraomohyoid neck dissection and free flap reconstruction was performed. The patient also underwent adjuvant chemoradiotherapy. No evidence of local recurrence or distant metastasis was detected during the 6 months of follow-up. Subsequently, the patient returned to her home country, and further follow-ups were not conducted.